N2 and N2O mitigation potential of replacing maize with the perennial biomass crop Silphium perfoliatum—An incubation study. Issue 10 (16th July 2021) - Kemmann, Björn; Wöhl, Lena; Fuß, Roland; Schrader, Stefan; Well, Reinhard; Ruf, Thorsten
Abstract: Sustainability of biogas production is strongly dependent on soil‐borne greenhouse gas (GHG) emissions during feedstock cultivation. Maize ( Zea mays ) is the most common feedstock for biogas production in Europe. Since it is an annual crop requiring high fertilizer input, maize cropping can cause high GHG emissions on sites that, due to their hydrology, have high N2 O emission potential. On such sites, cultivation of cup plant ( Silphium perfoliatum ) as a perennial crop could be a more environmentally friendly alternative offering versatile ecosystem services. To evaluate the possible benefits of perennial cup plant cropping on GHG emissions and nitrogen losses, an incubation study was conducted with intact soil cores from a maize field and a cup plant field. The 15 N gas flux method was used to quantify N source‐specific N2 and N2 O fluxes. Cumulated N2 O emissions and N2 +N2 O emissions did not differ significantly between maize and cup plant soils, but tended to be higher in maize soil. Soils from both systems exhibited relatively high and similar N2 O/(N2 +N2 O) ratios (N2 Oi). N2 O emissions originating from sources other than the 15 N‐labelled NO3 pool were low, but were the only fluxes exhibiting a significant difference between the maize and cup plant soils. Missing differences in fluxes derived from the 15 N pool indicate that under the experimental conditions with high moisture and NO 3 ‐ level, and without plants, the cropping system had little effect on N fluxes related to denitrification. Lower soil pH and higher bulk density in the cup plant soil are likely to have reduced the mitigation potential of perennial biomass cropping. Abstract : The sustainability of biogas production can be hampered by soil‐derived greenhouse gas (GHG) emissions during feedstock cultivation. We examined whether soil under a perennial biomass crop ( Silphium perfoliatum ) emits less GHG than soil under an annual crop ( Zea mays ). Intact soil cores from each crop were incubated for 18 days and processes involved in soil N2 O formation assessed using a novel stable isotope method. We found no significant differences between cup plant and maize soil, indicating that potential GHG mitigation through perennial cropping is not due to the impact of the cropping system on the soil properties affecting GHG emissions.